2021
DOI: 10.1101/2021.12.12.472247
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A two-component protein condensate of EGFR and Grb2 regulates Ras activation at the membrane

Abstract: We reconstitute a phosphotyrosine-mediated protein condensation phase transition of the ∼200 residue cytoplasmic tail of the epidermal growth factor receptor (EGFR) and the adaptor protein, Grb2, on a membrane surface. The phase transition depends on phosphorylation of the EGFR tail, which recruits Grb2, and the dimerization of Grb2, which provides the crosslinking element for condensation with EGFR. The Grb2 Y160 residue plays a structurally critical role in dimer formation, and phosphorylation or mutation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…More recently, we have shown that the Y160E Grb2 mutant is defective in promoting phase separation of scaffold proteins upon phosphorylation (C.‑W. Lin et al, 2021). In the present study, the use of Grb2-Y160E shows a reduction in the PLCγ2-peptide fusion phosphorylation by Btk, compared to the wild-type Grb2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, we have shown that the Y160E Grb2 mutant is defective in promoting phase separation of scaffold proteins upon phosphorylation (C.‑W. Lin et al, 2021). In the present study, the use of Grb2-Y160E shows a reduction in the PLCγ2-peptide fusion phosphorylation by Btk, compared to the wild-type Grb2.…”
Section: Resultsmentioning
confidence: 99%
“…The second possibility is that Grb2 alone promotes condensation of LAT (C.‑W. Lin et al, 2021), creating small domains of dense LAT, within which Btk cannot diffuse freely. The addition of SOS-PRR along with Grb2 induces the full phase transition of the phosphorylated LAT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that Grb2 is able to simultaneously bind Btk and LAT, thus slowing Btk molecules through an additional anchor point to the membrane (via the Grb2-LAT complex). The second possibility is that Grb2 alone has promoted small LAT condensates that are not immediately visible by eye ( Lin et al, 2021 ), creating small domains of dense LAT, within which Btk cannot diffuse freely. The addition of SOS-PRR along with Grb2 induces the full phase transition of the phosphorylated LAT ( Figure 5C and Figure 5—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 ] Recently, liquid–liquid phase separation (LLPS) of proteins induced by multivalent protein‐protein interactions emerged as a key principle driving dynamic receptor clustering. [ 15–21 ] Experimentally pinpointing and characterizing the involvement of LLPS in the formation and activation of signaling complexes in the plasma membrane has remained challenging due to the nanoscale dimensions and the high dynamics of such entities.…”
Section: Introductionmentioning
confidence: 99%